Stigmatisasi Penggunaan Nama Sapaan Di Kalangan Santri Pondok Pesantren Kyai Ageng Selo Dukuh Selogringging, Desa Tulung, Kecamatan Tulung, Kabupaten Klaten - Dewi Anggraini, Nita, Dra. Atiqa Sabardila M.Hum (2017)
This study aims to describe the shape Greeting Name Stigmatization Use Among Boarding School of Kyai Ageng Selo, Tulung Village, Tulung District, Klaten Regency, explained the reason behind the emergence of Greeting Name Stigmatization Use Among Boarding School of Kyai Ageng Selo, Tulung Village, Tulung District, Klaten Regency, and highlights the impact caused by Greeting Name Stigmatization Use Among Boarding School of Kyai Ageng Selo, Tulung Village, Tulung District, Klaten Regency. This research is a qualitative descriptive study content analysis research strategy. Methods of data collection is done through techniques see, interview techniques, and technical notes. Data were analyzed using methods unified referential, methods unified orthographic, and pragmatic unified method. The results showed: 1) The form of stigmatization greeting name, with regard to the original name, physical form, the names of animals, habit/hobby, position/title, character names, and the name of the food. 2) The reason behind the emergence of stigmatization greeting name, grouped by the sense of the physical form, the meaning of the title, the characteristic phonological, morphological traits, characteristic syntax. 3) The impact of the use of stigmatization greeting name, categorized into five categories: the effect was very happy, happy, ordinary, unhappy, and very unhappy. Keywords: stigmatization, greeting name.